Analysis of induced sputum in adults with asthma: identification of subgroup with isolated sputum neutrophilia and poor response to inhaled corticosteroids. - Green, R; Brightling, C; Woltmann, G; Parker, D; Wardlaw, A; Pavord, I (2002)
BACKGROUND: The debate as to whether asthma is a single or heterogeneous disease remains unresolved although pathological studies, mostly using fibreoptic bronchoscopy on small numbers of subjects, have emphasised the similarities between different clinical phenotypes. METHODS: Lower airway inflammation was assessed non-invasively using induced sputum in 34 normal controls and 259 adults with symptomatic asthma receiving treatment at steps 1-3 of the British Thoracic Society (BTS) guidelines. A subgroup of 49 patients treated with as required beta(2) agonists only who met BTS criteria for a step up in treatment were studied before and 2 months after treatment with inhaled budesonide 400 micro g twice daily. RESULTS: There was considerable heterogeneity in induced sputum cell counts, particularly in non-atopic patients. A subgroup of 60 patients had a distinctive sputum cell profile with a neutrophil count higher than our normal range (>65.3%) and a normal sputum eosinophil count (<1.9%). These patients were older, predominantly female, and were more likely to be non-atopic but otherwise had similar clinical and physiological features to the group as a whole. Among the 49 subjects studied before and after inhaled budesonide, 11 patients had an isolated sputum neutrophilia. Following treatment, these patients showed significantly less improvement in visual analogue symptom scores (-5.5 v -19.4 mm; mean difference 13.9; 95% CI 0.7 to 27.0), forced expiratory volume in 1 second (FEV(1)) (-0.08 v 0.13 l; mean difference 0.21; 95% CI 0.03 to 0.39), and concentration of methacholine provoking a fall in FEV(1) of 20% or more (PC(20)) (0.15 v 1.29 doubling doses; mean difference 1.11; 95% CI 0.13 to 2.15) than the remaining 38 patients. CONCLUSIONS: These results suggest the presence of a distinct subgroup of patients with mild to moderate asthma who have predominantly neutrophilic airway inflammation and who respond less well to treatment with inhaled corticosteroids.